2017
DOI: 10.1016/j.jvolgeores.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Fluid geochemistry of a deep-seated geothermal resource in the Puna plateau (Jujuy Province, Argentina)

Abstract: This study focused on the geochemical and isotopic features of thermal fluids discharged from five zones located in the high altitude Puna plateau (Jujuy Province between S 22°20′-23°20′ and W 66°-67°), i.e. Granada, Vilama, Pairique, Coranzulí and Olaroz. Partially mature waters with a Na + -Cl − composition were recognized in all the investigated zones, suggesting that a deep hydrothermal reservoir hosted within the Paleozoic crystalline basement represents the main hydrothermal fluid source. The hydrotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 71 publications
4
16
0
Order By: Relevance
“…Hilton et al, 1993;Fischer and Chiodini, 2015), the Rc/Ra values of the CBC samples are consistent with the abnormally thick crust of the Southern Puna (Heit et al, 2014), fitting well with those values from hydrothermal systems from the Central Andean Volcanic Zone (e.g. Tassi et al, 2010;Benavente et al, 2016;Peralta Arnold et al, 2017). As far as the δ 13 C-CO 2 values are concerned, they are consistent with those of mantle CO 2 (Rollinson, 1993;Sano and Marty, 1995;Hoefs, 1997;Ohmoto and Goldhaber, 1997).…”
Section: Origin Of Gasessupporting
confidence: 77%
See 1 more Smart Citation
“…Hilton et al, 1993;Fischer and Chiodini, 2015), the Rc/Ra values of the CBC samples are consistent with the abnormally thick crust of the Southern Puna (Heit et al, 2014), fitting well with those values from hydrothermal systems from the Central Andean Volcanic Zone (e.g. Tassi et al, 2010;Benavente et al, 2016;Peralta Arnold et al, 2017). As far as the δ 13 C-CO 2 values are concerned, they are consistent with those of mantle CO 2 (Rollinson, 1993;Sano and Marty, 1995;Hoefs, 1997;Ohmoto and Goldhaber, 1997).…”
Section: Origin Of Gasessupporting
confidence: 77%
“…Between dashed lines, average values for Andean Volcanic Arc (Hoke et al, 1994) and crustal gases (Hilton et al, 2002), (c) CO 2 / 3 He vs. δ 13 C-CO 2 ‰ binary diagram for the gases from the Cerro Blanco Caldera. Isotopic values from others geothermal systems in the Puna plateau (Peralta Arnold et al, 2017) are shown for comparison. Symbols are: red triangle: bubbling gases from Los Hornitos area; green circle: dissolved gases from El Médano area; green pentagon: fumarolic gas sample; black square: data from Peralta Arnold et al, (2017).…”
Section: Temperature Estimations Of the Hydrothermal Reservoirmentioning
confidence: 99%
“…Moreover, the SiO 2 geothermometer gives only the minimum temperature of the geothermal reservoir [29]. It should be noted that the SiO 2 geothermometer depends on dilution and steam loss, while the equilibrium temperatures estimated by using other geothermometry techniques, based on the chemical equilibria in Na-K-Mg systems, are less influenced by dilution and steam loss [30].…”
Section: Geochemistry Temperature Scale and Water-rock Balancementioning
confidence: 99%
“…Thermal spring geochemistry is controlled by the depth of fluid circulation, the types of rocks encountered along fluid flow paths, water-rock interactions along these pathways, and the degree of mixing with shallow meteoric groundwater (e.g., Fournier, 1989;Arnold et al, 2017). These factors are closely tied to the overall tectono-magmatic setting, and spring chemical and isotopic composition (e.g., He, C, O, S) can inform the relative contribution from magmatic, crustal, and meteoric sources (Hilton, 1996;van Soest et al, 1998;de Hoog et al, 2001;Hilton et al, 2002;Zimmer et al, 2004;Newell et al, 2008;Sano et al, 2009;Scott et al, 2020).…”
Section: List Of Tablesmentioning
confidence: 99%
“…High subsurface temperatures and a long flow path will increase the concentrations of ions at the surface. BAS generally have higher concentrations of Na + , K + , total Fe, Ba, and As, indicative of water-rock interaction during fluid flow and interaction with relatively young volcanic rocks (Hilton et al, 1996;Arnold et al, 2017).…”
Section: Geochemistry Of Spring Systemsmentioning
confidence: 99%